How Effective Are Active Labor Market Policies in Developing Countries? : A Critical Review of Recent Evidence - McKenzie, David (World Bank, Washington, DC, 2017)
Jobs are the number one policy concern of policy makers in many countries. The global financial crisis, rising demographic pressures, high unemployment rates, and concerns over automation all make it seem imperative that policy makers employ increasingly more active labor market policies. This paper critically examines recent evaluations of labor market policies that have provided vocational training, wage subsidies, job search assistance, and assistance moving to argue that many active labor market policies are much less effective than policymakers typically assume. Many of these evaluations find no significant impacts on either employment or earnings. One reason is that urban labor markets appear to work reasonably well in many cases, with fewer market failures than is often thought. As a result, there is less of a role for many traditional active labor market policies than is common practice. The review then discusses examples of job creation policies that do seem to offer promise, and concludes with lessons for impact evaluation and policy is this area.